2016
DOI: 10.1159/000453661
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and Plaque Psoriasis: Preliminary Investigation in a Clinical Sample of 250 Patients

Abstract: Background/Aims: Psoriasis as a dermatological disorder has complex effects on mental health and the psychological status of the patient. Many authors proposed that assessing how psoriasis affects a patient's life is better than a body surface area measurement for delineating psoriasis severity. Alexithymia is a personality dimension characterized by difficulty identifying feelings, difficulty describing feelings, and externally oriented thinking observed in many clinical conditions, especially in psychosomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 29 publications
(21 reference statements)
2
24
1
2
Order By: Relevance
“…Alexithymia represents a personality trait characterized by the lack of understanding, processing, and describing emotions, reflecting the tendency to have reduced symbolic thinking, limited fantasy life, externally oriented cognitive thinking, difficulty in distinguishing feelings from bodily sensations, and inadequacy in empathy and intuition [12]. This personality trait has been observed in some chronic inflammatory skin disorders, including psoriasis and hidradenitis suppurativa (HS) [13][14][15], but no association has been found with other skin diseases, such as acne and seborrheic dermatitis [16,17]. Because alexithymia has been poorly investigated in AD, this multicentric study aimed to investigate its prevalence in AD patients, and its correlation with demographic and clinical variables.…”
Section: Introductionmentioning
confidence: 99%
“…Alexithymia represents a personality trait characterized by the lack of understanding, processing, and describing emotions, reflecting the tendency to have reduced symbolic thinking, limited fantasy life, externally oriented cognitive thinking, difficulty in distinguishing feelings from bodily sensations, and inadequacy in empathy and intuition [12]. This personality trait has been observed in some chronic inflammatory skin disorders, including psoriasis and hidradenitis suppurativa (HS) [13][14][15], but no association has been found with other skin diseases, such as acne and seborrheic dermatitis [16,17]. Because alexithymia has been poorly investigated in AD, this multicentric study aimed to investigate its prevalence in AD patients, and its correlation with demographic and clinical variables.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have investigated the prevalence of alexithymia in adult patients with psoriasis. The observed prevalence of alexithymia in patients with psoriasis ranges between 15·6% and around 33% . Our study showed that patients with psoriasis with difficulty in identifying and expressing emotions were characterized by high psoriasis burden, including markedly reduced quality of life, high prevalence of anxiety and depression, and high risk of alcohol dependency.…”
mentioning
confidence: 62%
“…To our knowledge, this is the first longitudinal study evaluating the change in the ability of patients with psoriasis to identify and describe emotions during treatment. In fact, the existing studies were cross‐sectional . Only a longitudinal design may allow evaluation of changes over time and evaluation of the complex association between alexithymia, disease severity and disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…Alexithymia is also defined as a personality trait which manifests itself in comorbidity with different physical and psychopathological disorders (Lumley et al, 2005 , 2007 ; Mattila et al, 2009 ; Honkalampi et al, 2010 ; Tolmunen et al, 2011 ; Marchetti et al, 2019 ) and retained as a transient variable state related to both psychopathological conditions and stress levels (Pollatos et al, 2011 ). Also, alexithymia seems to be involved in the pathogenetic mechanism of several somatic illness (Porcelli et al, 1996 ; Willemsen et al, 2008 ; Mazaheri et al, 2012 ; Talamonti et al, 2016 ; Marchi et al, 2019 ; Martino et al, 2020c ) and it appears to be associated with depression and anxiety in patients with type 2 diabetes (T2DM) (Friedman et al, 2003 ; Luminet et al, 2006 ; Pouwer et al, 2010 ; Sapozhnikova et al, 2012 ; Shinkov et al, 2018 ). Alexithymia and psychological distress, as anxiety and depression, may impair patient's compliance and adherence, concurring in a worst clinical presentation and course of a chronic disease (Sapozhnikova et al, 2012 ; Hintistan et al, 2013 ; Mnif et al, 2014 ; Stanton and Hoyt, 2017 ; Marchini et al, 2018 ; Settineri et al, 2019 ; Vicario and Martino, 2020 ; Vicario et al, 2020 ; Vita et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%